High Fat Diet-Induced miR-122 Regulates Lipid Metabolism and Fat Deposition in Genetically Improved Farmed Tilapia (GIFT, Oreochromis niloticus) Liver - Qiang, Jun; Tao, Yi Fan; Bao, Jing Wen; Chen, De Ju; Li, Hong Xia; He, Jie; Xu, Pao (Frontiers in Physiology, 2018)
The liver is an important organ for the regulation of lipid metabolism. In genetically improved farmed tilapia (GIFT, Oreochromis niloticus), fat deposition in the liver occurs when they are fed high-lipid diets over a long term. This can affect their growth, meat quality, and disease resistance. MicroRNAs (miRNAs)are known to be crucial regulatory factors involved in lipid metabolism; however, the mechanism by which they regulate lipid deposition in GIFT remains unclear. Comparative miRNA expression profiling between GIFT fed a normal diet and those fed a high-lipid diet showed that miR-122 is closely related to lipid deposition. Using miR-122 as a candidate, we searched for a binding site for miR-122 in the 3′-untranslated region (UTR) of the stearoyl-CoA desaturase gene (SCD)using bioinformatics tools, and then confirmed its functionality using the luciferase reporter gene system. Then, the regulatory relationship between this miRNA and its target gene SCD was analyzed using real-time polymerase chain reaction (qRT-PCR) and western blotting analyses. Last, we investigated the effect of the loss of miR-122 expression on lipid metabolism in GIFT. The results showed that a sequence in the 3′-UTR region of SCD of GIFT was complementary to the miR-122 seed region, and there was a negative relationship between the expression of miRNA and SCD expression. Inhibition of miR-122 up-regulated SCD, increased the expression of fat synthesis-related genes, increased hepatic triglyceride and cholesterol contents, and promoted weight gain in fish. Our results showed that miR-122 targets SCD to mediate hepatic fat metabolism. These results provide new insights for the prevention and treatment of fatty liver disease in GIFT.